Decreased influenza vaccination coverage among Chinese healthcare workers during the COVID-19 pandemic - Libing Ma; Xuan Han; Yuan Ma; Yuan Yang; Yunshao Xu; Di Liu; Weizhong Yang; Luzhao Feng (BMC, 2022)
Abstract Background Healthcare workers (HCWs) were the priority group for influenza vaccination, in China during the 2020/2021 and 2021/2022 influenza seasons. However, vaccination rates in HCWs have always been low. This study investigated influenza vaccination status among Chinese HCWs and analyzed the factors driving vaccination. Methods We provided electronic questionnaires to HCWs from January 27, 2022 to February 21, 2022, using the WeChat platform "Breath Circles". HCWs who received the link could also forward it to their colleagues. Binary logistic regression models were used to analyze vaccination-associated factors among HCWs. Results Among the 1697 HCWs surveyed, vaccination coverage was 43.7% (741/1697) during the 2020/2021 influenza season, and 35.4% (600/1697) during the 2021/2022 influenza season, as of February 21, 2022. Additionally, 22.7% (385/1697) and 22.1% (358/1697) of HCWs reported that their workplaces implemented a free vaccination policy for all employees during the 2020/2021 and 2021/2022 influenza seasons. HCWs who were required to be vaccinated according to hospital regulations, and whose hospitals implemented the free influenza vaccine policy were more likely to be vaccinated (2020/2021 and 2021/2022; P < 0.05). In addition, the economic level of the HCWs' province (2021/2022, P < 0.05) and the HCWs' knowledge about vaccination and willingness to get vaccinated, such as active learning about vaccines (2020/2021, P < 0.05), supportive attitude toward vaccination for all HCWs (2020/2021 and 2021/2022; P < 0.05), also had an impact on vaccine coverage. Conclusions A free influenza vaccination policy and workplace required vaccination are effective in improving influenza vaccination coverage among HCWs. Influenza vaccination coverage of Chinese HCWs remained low and showed a downward trend after the COVID-19 outbreak. Further effective measures, such as advocacy campaigns, free vaccine policies, and on-site vaccination could be implemented to improve influenza vaccination coverage. Graphical abstract